Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

Femmes de spectacle au XIXe siècle - Ponzetto, Valentina; Fix, Florence (2022)
Quelle est la place des femmes dans l’industrie du spectacle du XIXe siècle au-delà des métiers de performance très exposés qu’exercent les actrices, ...
ISSN: 1376-3199
Keywords: Sophie-Anne

#MeToo et la justice réparatrice (Curio.ca, 2022)
Ça fait plus de 5 ans que le mouvement #MeToo (#MoiAussi) a commencé. Depuis, de nombreuses victimes de crimes sexuels critiquent notre système de justice traditionnel. Mais il existe une autre solution, fondée sur des principes et des processus autochtones : la justice réparatrice. Comment fonctionne-t-elle exactement? Tom-Éliot Girard est …
Keywords: Coffre à outils; Nettoyer; À ajouter

La Circassienne: A Study of the Female Circus Artist in French Literature - Menninga, Crystal (Masters Theses, 2022)

Edgar Fruitier est libre après moins d’un mois de prison - Radio-Canada (Radio-Canada, 2022)
Son risque de récidive est jugé faible en raison de son état physique et mental.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Le mouvement #MoiAussi et ses événements marquants - Pineda, Améli (Le Devoir, 2022)
En octobre 2017 émergeait un mouvement de dénonciation planétaire.
Keywords: Bibliographie; Nettoyer

La littérature après #MoiAussi - Hébert-Dolbec, Anne-Frédérique (Le Devoir, 2022)
Le milieu littéraire attend encore des changements structurels importants, cinq ans après le début du mouvement.
Keywords: Bibliographie; Nettoyer

Politique visant à prévenir et combattre les violences à caractère sexuel - École nationale de théâtre du Canada (2022)
Keywords: Bibliographie; Nettoyer

Une nouvelle accusation contre Eddy Toussaint: Son école de danse change de nom pour se dissocier du chorégraphe - Duhamel, Frédérik-Xavier (La Presse, 2022)
Alors que le chorégraphe Eddy Toussaint fait face à une deuxième accusation d’agression sexuelle, l’école et la troupe de ballet qu’il a fondées prennent leurs distances et changent de nom. Des spectacles ont aussi été retirés de l’affiche dans la foulée des accusations, mais la direction estime qu’il est injuste de pénaliser les danseurs.
Keywords: Bibliographie; Nettoyer

Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

La relation de pouvoir entre un professeur et ses étudiantes - Radio-Canada (Tout un matin, 2022)
Tout un matin | L'ex-professeur de littérature Samuel Archibald aurait commis des « violences à caractère sexuel » et du « harcèlement sexuel » envers deux étudiantes avec lesquelles il était en situation d'autorité en tant que directeur de maîtrise. Le lien d'emploi entre l'auteur et l'Université du Québec à Montréal (UQAM) aurait été rompu l'année dernière. Au micro de Tout un matin, Rachel Chagnon, professeure au Département des sciences juridiques de l'UQAM, définit ce qu'est une relation de pouvoir entre un enseignant et un étudiant (ce sont majoritairement des femmes), principe qui se trouve au cœur de la politique de l'université pour prévenir et combattre les violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions sexuelles contre Win Butler : des radios boycottent Arcade Fire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2022)
Trois femmes font état d’interactions inappropriées, une autre dit avoir été agressée sexuellement en 2015.
Publisher: Radio-Canada.ca

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1886141
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Gros été pour la culture du viol - Elkouri, Rima (La Presse, 2022)
Nouveau scandale de viol collectif à Hockey Canada. Allégations d’inconduites sexuelles contre l’humoriste Philippe Bond. Absolution conditionnelle pour l’ingénieur Simon Houle coupable d’agression sexuelle…
Keywords: Bibliographie; Nettoyer

Philippe Bond était déjà sur des listes noires - Bélanger, Cédric (Le Journal de Québec, 2022)
L'humoriste Philippe Bond était déjà depuis plusieurs années sur la liste noire de grandes organisations culturelles.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix (2022)
Lisez tous nos articles, analyses et opinions sur les allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix. Le Devoir, le quotidien indépendant par excellence au Québec depuis 1910.

Julien Lacroix, Maripier Morin... Le retour des personnalités dénoncées fait mal - Cazzaniga, Constance (Métro, 2022)

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Capsules sur le harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2022)
Le Groupe d’aide et d’information sur le harcèlement au travail (GAIHST) lance 5 capsules vidéo dédiées aux travailleurs(euses) du Québec.
https://gaihst.qc.ca/capsules
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Number: 24 Publisher: Ghent University
Keywords: #metoo; Irina; consentement; lecture féministe; lecture littéraire; violences sexuelles

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Poursuite intentée par Gilbert Rozon: La requête de Julie Snyder et Pénélope McQuade rejetée en appel - Morin-Martel, Florence (La Presse, 2022)
La poursuite de Gilbert Rozon réclamant 450 000 $ à Julie Snyder et Pénélope McQuade pour diffamation ira de l’avant. La requête des deux animatrices visant à mettre fin aux procédures, qui relèvent « d’une poursuite-bâillon », selon elles, a été déboutée en Cour d’appel, vendredi.
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Publisher: SAGE Publications Ltd
Keywords: Myriam; TV; TV production; Television

Vague de suicides chez les artisans de la scène: Quand le rideau tombe à jamais - Blais-Poulin, Charles-Éric; Groguhé, Marissa (La Presse, 2022)
Keywords: Bibliographie; Nettoyer

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2020.1759114
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Entente collective 2022-2024 entre l'Orchestre Métropolitain et la Guilde des musiciens et musiciennes du Québec (2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Soutien psychologique (Guilde des musiciens et musiciennes du Québec, 2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

#MeToo and beyond: perspectives on a global movement - Alcalde, M. Cristina; Villa, Paula-Irene (University Press of Kentucky, 2022)

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

Rapport de recherche sur l’éthique en regard des violences à caractère sexuelle dans le milieu de l’humour québécois francophone - Bernier, Dominique; Paré, Christelle; Carbonneau, Karine; Vernus, Judith; Morency, Sophie-Anne (UQÀM et partenaires, 2022)
Rapport interne
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Musicaction, 2022)
Rapport d’étude réalisé pour et avec la collaboration de la Fondation Musicaction, grâce à l’appui du Gouvernement du Canada
Keywords: Bibliographie; Nettoyer

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Publisher: Berkeley Journal of Gender, Law & Justice
Keywords: Bibliographie; Nettoyer

Révision des lois sur le statut de l'artiste - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2022)
QUÉBEC, le 3 juin 2022 /CNW Telbec/ - L'Assemblée nationale du Québec a adopté à l'unanimité aujourd'hui le projet de loi numéro 35, Loi visant à moderniser et à harmoniser les règles relatives au statut professionnel de l'artiste, déposé par la ministre...
Keywords: Bibliographie; Nettoyer

Les violences sexistes après #MeToo (Presses des Mines, 2022)
''À partir d'octobre 2017, #MeToo devient un phénomène mondial, en diffusant internationalement le slogan que Tarana Burke, militante new-yorkaise contre les violences sexuelles, avait lancé dix ans plus tôt. Une multitude de victimes témoignent sur divers supports numériques et médiatiques, reformulant et intensifiant des luttes féministes en cours contre les violences sexistes. À l'initiative d'une nouvelle génération de chercheuses et chercheurs francophones sur les violences de genre, ce premier ouvrage académique en France sur #MeToo cherche à comprendre l'événement. Il propose une approche empirique de ce mouvement mondial. Il décrypte d'abord l'événement #MeToo dans sa matérialité, ses contextes de réception et d'appropriation et s'efforce de montrer comment l'usage des réseaux socionumériques permet d'articuler de nouvelles formes de militantisme ou de renforcer des pratiques militantes existantes en ligne et hors ligne. Il inscrit ensuite #MeToo dans une histoire des luttes féministes de plus long terme et s'efforce de questionner son unité à travers l'étude de ses résonances contrastées dans différents milieux professionnels.''– Site de l'éditeur
OCLC: 1354535098

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

Recommandations de l’équipe à l’issue de trois phases d’une programmation de recherche partenariale université/collectivités - Collectif de recherche Justice pour les femmes victimes de violence (Service aux collectivités de l’Université du Québec à Montréal /Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale /Concertation des luttes contre l’exploitation sexuelle /Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel, 2022)

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Cadre de référence évolutif des objectifs et contenus de prévention des violences à caractère sexuel en milieu d’enseignement supérieur - Fradette-Drouin, Laurie; Bergeron, Manon (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur. Université du Québec à montréal, 2022)
Keywords: Bibliographie; Nettoyer

Loi sur le statut professionnel des artistes des arts visuels, du cinéma, du disque, de la littérature, des métiers d’art et de la scène - Gouvernement du Québec (2022)

*Loi visant à harmoniser et à moderniser les règles relatives au statut professionnel de l'artiste - Gouvernement du Québec (2022)
Keywords: Bibliographie; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.
Accepted: 2022-03-30T06:27:19Z Publisher: Taideyliopiston Sibelius-Akatemia

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Pour une culture du consentement - Les frères Seaborn (2022)
Place: Montréal Publisher: Société Radio-Canada
Keywords: Bibliographie; Nettoyer

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Accepted: 2023-02-20T11:59:11Z
Keywords: Bibliographie; Irina; Nettoyer

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Alexandra, Kiernan Steiner (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Num Pages: 14
Keywords: Jazz; Music; Myriam

La justice réparatrice en matière de violences sexuelles : L’expérience de dialogue entre personnes victimes et personnes auteures dans les cas de violences sexuelles - Marceau, Laurence (2022)

L'artiste et son oeuvre - McEwen, Jérémie (2022)
Keywords: Bibliographie; Nettoyer

Briser le rideau de verre en humour - Morency, Sophie-Anne; Cézard, Zed; Carbonneau, Karine (2022)
Keywords: Sophie-Anne

Morinom - Office québécois de la langue française (Grand dictionnaire terminologique, 2022)
Prénom qui a été donné à une personne à sa naissance, mais que celle-ci ne souhaite plus qu'on emploie pour la désigner.
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Que reste-t-il de #MoiAussi?: secousses québécoises d'un mouvement planétaire - Pineda, Améli (Somme toute : Le Devoir, 2022)
"Au Québec, la vague #MoiAussi qui déferle jusqu'à ce jour a pris son essor les 18 et 19 octobre 2017, lorsque des enquêtes du Devoir et de La Presse ont déboulonné deux géants du monde des médias. C'est avec cet épisode critique que s'ouvre le livre d'Améli Pineda, qui entamait alors sans le savoir plusieurs années de couverture du phénomène des dénonciations d'abus sexuels à grande échelle. À l'intersection des mondes des médias, de la justice et de l'activisme, ce texte synthétise et contextualise les cinq ans du mouvement #MoiAussi au Québec, dépeignant ses plus grands moments et relatant la réaction en chaîne du public et des magistrats. Améli pineda s'appuie sur des articles phares parus depuis 2017 dans Le Devoir ainsi que sur une pléiade d'entrevues menées auprès des protagonistes du mouvement - femmes ayant dénoncé, homme visés par des allégations, avocates et avocats, chercheuses, créatrices de pages de dénonciations virtuelles - ainsi que sur son expérience personnelle de l'effervescence médiatique des cinq dernières années pour trouver un sens à cette prise de conscience collective qui a transformé notre société."–back cover
OCLC: 1346354564

Dénoncé en ligne, Yann Perreau est lui aussi largué par sa maison de disques - Radio-Canada (Radio-Canada, 2022)
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

Sex, consent and justice: a new feminist framework - Sikka, Tina (Edinburgh University Press, 2022)

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann (Éditions du remue-ménage, 2022)
Keywords: Bibliographie; Nettoyer

Justice pour les femmes marginalisées victimes de violences sexospécifiques : Ce que la littérature et les intervenantes nous apprennent - Thibault, Sarah; Pagé, Geneviève; Boulebsol, Carole; coll. (Service aux collectivités de l’Université du Québec à Montréal / Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale / Concertation des luttes contre l’exploitation sexuelle / Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel., 2022)

Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

Jouer Sur le Banc Les Filles Dans le Monde de L'improvisation. - Walsh-Viau, Emmanuelle.; Joubert, Lucie (Somme Toute, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne